(untitled) (ADI Journal on Recent Innovation (AJRI), 2022)
The Covid-19 pandemic has made most people aware of the importance of health, so they want to try harder to be healthy and have robust immune systems. This also influences travel patterns, where most tourists visit the outdoors and wish to engage in sports and recreational activities when travelling. One of Bali’s districts with natural and cultural wealth is Gianyar Regency. With all this potential, it will be possible to develop sports tourism combined with the unique cultural tourism of Gianyar Regency to create uniqueness compared to other sport tourism destinations. The aims of this research were (1) to identify the potential for sports tourism in Gianyar Regency and (2) to identify obstacles in the development of sport tourism in Gianyar Regency, (3) to develop a strategy for developing sports tourism in Gianyar Regency as post-covid-19 tourism recovery. The method used in this research is the SWOT Analysis and IFAS - EFAS Matrix. The result showed Gianyar is in Quadrant I, where the strategy leads to growth and build. It also has a big chance to develop sports tourism for the tourism recovery after the Covid-19 pandemic. The strategies that can be implemented are developing sport tourism packages by collaborating on cultural tourism with sports tourism, conducting an analysis with stakeholders regarding the potential for natural damage caused by sports tourism, conducting socialization to the surrounding community about sports tourism, involving and providing training to sports activity experts sports on tourism, and make guidelines for each type of sports tourism to be developed.